Inverse problems for stochastic transport equations. (6th January 2015) - Crisan, Dan; Otobe, Yoshiki; Peszat, Szymon
Abstract: Inverse problems for stochastic linear transport equations driven by a temporal or spatial white noise are discussed. We analyse stochastic linear transport equations which depend on an unknown potential and have either additive noise or multiplicative noise. We show that one can approximate the potential with arbitrary small error when the solution of the stochastic linear transport equation is observed over time at some fixed point in the state space.